Relación entre síndrome de Burnout y riesgo psicosocial intralaboral en profesionales sociales (2021)
The objective of this research was to identify the relationship between the burnout syndrome and psychosocial risk conditions within the workplace in social professionals. In relation to the methodology, a non-experimental cross-sectional design was carried out for a non-probabilistic sample of 76 professionals. The data analysis plan was developed from a model of structural equations. The results indicated that there are significant relationships between work demands, control over work and rewards with the domain of emotional burnout, as well as between work demands and the depersonalization domain in the burnout syndrome. These relationships, being significant, contribute to the model of structural equations where it is possible to establish, in first place, that there is a relationship between the study variables and that psychosocial risk within the workplace explains burnout in 47.8%.